Sustainability of the EU-28 Trade with China and the USA - Hilmola, Olli-Pekka; Panova, Yulia (Economy of Regions, 2021)
There has been a lot of debate in global politics about fair trade, surpluses (also called positive trade accounts), and deficits (negative trade accounts) among the USA, China and the European Union (EU). The study aims to analyse the countries’ trade accounts through the lenses of international finance theory. Based on financial analytical models, the countries’ competitiveness and changes in their net foreign wealth were examined. The factors considered in the literature review are as follows: exchange rate, government tariff and tax policies, saving rate, manufacturing base, investments, natural resource abundance and others. The computation of the trade accounts was conducted using the ten-year international trade data (2009-2018) for the EU-28 member countries that became the main importer for China instead of the USA in 2019. The conducted empirical research showed that Chinese trade has continuous deficits throughout European countries, and in some countries, it could be considered as an increasingly important structural issue (for example, in Poland and the Czech Republic). Trade with the USA, in turn, typically produces surplus for European countries, where Germany is the leader. The provided conclusions hold value for international trade managers in terms of their potential influence on public policy in the researched countries. In light of the financial crisis, the current export shock could be used by countries as an occasion to change the course and depart from the assumptions, which do not advocate for free trade.